A disaster always rings twice: Early life experiences and central bankers' reactions to natural disasters. (15th June 2021) - Aslam, Maqsood; Farvaque, Etienne; Malan, Franck
Abstract: We analyze the impact of natural disasters experienced in the early life of central bankers to assess their reaction to present‐day similar events. We use a panel dataset covering 68 (developed and developing) countries, for the period 2000 Q1 to 2017 Q4, to examine how the very‐short‐run dynamics of inflation is affected by the (actual) natural disasters, and how past experiences affect the immediate reaction of central bankers to these shocks. Our results reveal that the effect of early‐life experiences is significant: central bankers who have been exposed to disasters in early life tend to manage inflation in a more conservative way in the very‐short‐run. The effect disappears over the course of one year, and central bankers with superior voting power have a larger influence on outcomes. Younger central bankers are more conservative than older ones, which may reveal that the early‐life disasters' impact decays over time. The European Central Bank (ECB) appears immune to such influences, in conformity with expectations given the ECB's federal architecture and the size of the area it administers. The behavior revealed by our results thus signifies that central banks tend, on average to avoid any inflationary bias, inducing that the long‐run impact of a disaster suffered in the formative years of an individual can bring socially positive consequences, when such an individual becomes governor of her country's central bank.